A Critical Reflection on the Sequencing of Content Related to the Concept of Ion in NCERT Class IX Science Textbook - Mehta , Sonam; Yadava, Shalini (SCHOOL SCIENCE, 2025)
Curricular textbooks prescribed by the respective boards, metaphorically, form the content Bible both for the teacher and the learner working at the grass root level. Teachers look up to the curricular textbooks as the guiding resource for the amount of content to be covered, the various subtopics and related topics to be dealt with and with prescribed extent of detailing. The present paper brings forth critical reflections of a TGT Chemistry teacher, teaching in a CBSE affiliated private school of Delhi since the past 13 years, who over years of teaching has been struggling with the sequencing of the content related to the concept of ion, mentioned in the NCERT textbook. The present paper is based on ‘Action research’ by the teacher to find out the most logical sequencing of the subtopics related to the content, which promotes conceptual understanding and discourages rote learning in the topic, which otherwise becomes a textbook compulsion. The paper presents alternative sequencing of content, which if suggestively changed in the NCERT Class IX Science textbook, then it will better portray the conceptual underpinnings of the content related to ion in a more transactionally and conceptually effective way.